1985
DOI: 10.1152/ajpheart.1985.248.6.h804
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic microcirculatory failure after ischemia and reperfusion: improvement with ATP-MgCl2 treatment

Abstract: Hepatic ischemia followed by reflow results in a myriad of metabolic and circulatory derangements that may eventually result in liver failure and death. In the present experiments we have used the technique of intravital fluorescence microscopy with fluoroscein isothiocyanate conjugated to bovine serum albumin as the intravascular fluorochrome to study the effects of ischemia and reperfusion on the hepatic microcirculation in vivo. Total hepatic ischemia was produced for 90 min to the left and median lobes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 0 publications
5
49
1
Order By: Relevance
“…With respect to the decreased hepatic blood flow, it has been reported that hepatic blood flow during the early stage of reperfusion is 30% to 75% of the initial values in an ischemic model [41]. Moreover, Clemens et al [38] reported that the number of perfused sinusoids on the surface of liver lobes was decreased after ischemia and reperfusion, which is consistent with our findings that C HbO and StO 2 remained lower than baseline values after reperfusion. While the exact mechanism related to the reduced C HbO remains unclear, involvement of reperfusion injury might be responsible.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With respect to the decreased hepatic blood flow, it has been reported that hepatic blood flow during the early stage of reperfusion is 30% to 75% of the initial values in an ischemic model [41]. Moreover, Clemens et al [38] reported that the number of perfused sinusoids on the surface of liver lobes was decreased after ischemia and reperfusion, which is consistent with our findings that C HbO and StO 2 remained lower than baseline values after reperfusion. While the exact mechanism related to the reduced C HbO remains unclear, involvement of reperfusion injury might be responsible.…”
Section: Discussionsupporting
confidence: 92%
“…However, we have not observed perfusion failure in entire liver lobules (shown in Fig. 4) following 10 minutes of portal triad occlusion, which is in contrast to studies of hepatic microcirculation after a longer period of ischemia (90 min) [38] and reperfusion (3 hours) [39]. The longer period of occlusion is characterized by a noticeable decrease in densely perfused sinusoids and is associated with an increased number of non-perfused liver lobules [39].…”
Section: Discussioncontrasting
confidence: 79%
“…Liver. It was claimed many years ago that infusion of ATP-MgCl 2 improved hepatic function and survival after hepatic ischemia (Hirasawa et al, 1980;Ohkawa et al, 1983;Frederiks and Fronik, 1986;Jeong and Lee, 2000) and after reperfusion (Clemens et al, 1985b). It has been claimed that the beneficial effect of ATP-MgCl 2 treatment after trauma-hemorrhage is associated with a downregulation of circulating levels of the inflammatory cytokines TNF and IL-6 (Wang et al, 1992c).…”
Section: Ischemiamentioning
confidence: 99%
“…[5][6][7] In fact, studies have suggested that such perfusion deficits were an essential first step toward injury to the liver parenchyma. 8,9 However, work by our laboratory and others have been unable to provide a link between perfusion deficits and remote organ injury. For example, remote injury to the mucosa of the small intestine has been reported during sepsis, despite unaltered microvascular perfusion.…”
mentioning
confidence: 93%